Wanita Agen Transformasi Sosial (Women as Agents of Social Transformation) - Safei, Su'aidi (Embassy of Malaysia in Cairo, Egypt, 2012)
Women as 50% of the population of Malaysia also contributed in all sectors of life and this fact couldn't be marginalized and disregarded. The slogan "Young Blood Shapes the Future" reminds us of the great role of women in the preservation of our country.